La metáfora del mirar en Nicolás de Cusa - Marinho Nogueira, Maria Simone (Anales del Seminario de Historia de la Filosofía, 2003)
At the beginning of De Visione Dei, Nicholas of Cusa puts us before an icon of the divine glance and invites us to an experimentation – initially surrounded by the metaphorical reflection – of the mystic contemplation. Working with the metaphor of the glance, the Cusano leaves us before the Creator’s look and the creature’s look. In the De Visione Dei, the divine look is creator and lover. The God’s look sees, creates and loves. This way, the present work will look for to meditate on the importance of the glance, seeking in the De Visione Dei a way to relate the multiplicity of the created look with the unit of the creator look.